The Effect of Critical Thinking Skills on Social Science Learning Outcomes - Habibah, Kurnia; Atmojo, Idam Ragil Widianto; Supianto, Supianto (Universitas Sebelas Maret, 2025)
This study aims to analyze the influence of critical thinking skills on the learning outcomes of Natural and Social Sciences (IPAS) of grade IV elementary school students. This study uses a quantitative approach with a correlational research model, because it focuses on the relationship between the variables of critical thinking ability and social studies learning outcomes. The research sample amounted to 64 students taken from a population of 178 grade IV students in Purwantoro District, Wonogiri Regency, using cluster random sampling techniques. The research instrument consisted of a critical thinking ability description test developed based on five indicators (identifying problems, analyzing arguments, stating reasoning, drawing conclusions, and solving problems) and a multiple-choice test of science learning outcomes. The data was analyzed using a simple linear regression test with the help of SPSS software version 25.0. The results showed that there was a positive and significant influence between critical thinking skills on social studies learning outcomes with a significance value of 0.000 < 0.05 and a determination coefficient value (R²) of 0.791, which means that the contribution of critical thinking skills to learning outcomes reached 79.1%. Thus, critical thinking skills have proven to be an important factor in improving the achievement of IPAS learning outcomes, and need to be developed systematically in the learning process in elementary schools.